Effect of Comprehensive Balance Modulating Strategies on Physical Performance Among the Elderly in Care Home Settings in Southern India - Mathew K. V., Binoy; Alagesan, Jagatheesan; Suganthirababu, Prathap (Curēus (Palo Alto, CA), 2024)
Purpose Globally, the proportion of the elderly population is rising. Age-related physical performance impairments are more common and affect quality of life. This study aimed to investigate the impact of a new exercise regimen called Comprehensive Balance-Modulating Strategies (CBMS) on the physical performance of older adults living in care home settings. Methods Forty-eight functionally independent elderly individuals were randomized into two groups: group A received the CBMS programme for eight weeks, and group B received routine medical care. The Short Physical Performance Battery (SPPB) and the Four Square Step Test (FSST) were outcome measures. Outcomes were measured at baseline, immediately after the intervention, and eight weeks after the intervention. Results The mean and standard deviation of subjects' ages in both groups were 72.46 (8.28) and 68.12 (6.95), respectively. The CBMS programme significantly improved physical performance among the intervention group ( = <0.0001). Conclusion The present study found that CBMS was effective in improving physical performance among institutionalized elderly. Large-scale clinical trials and research exploring the effect of CBMS among community-dwelling elderly individuals are recommended.